Fishery resource characteristics and stockassessment of ribbonfish, Trichiurus lepturus(Linnaeus) - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
Ribbonfish, Trichiurus lepturus (Linnaeus) has become one of the mostimportant exploited resources in the northwest coast of India. It was landed asbycatch of shrimp trawler earlier but on account of emerging export demand itis now increasingly targeted. The resource has been monitored for more thanten years. The landings of ribbonfishes varied between 16,000 t (1995) and63,000 t (2000) with an average catch of 33,000 t. The trawl contributed about93 % of the total landing. Peak catch rates were observed in September andNovember-December. T. lepturus is a carnivorous predator feeding oncrustaceans, fishes and cephalopods. Spawning season is prolonged fromOctober-May. Individual fish spawns once in a year and the minimum size atmaturity is 75 cm. The fecundity varied between 4,900 and 81,000 with a relativefecundity of 65 ova/gm of body weight.It grows at faster rate and attains 65.1 cm, 98.0 and 114.7 cm. at the end offirst, second and third year respectively. The estimated Lâ€ is 127.3 cm. and K0.67 (annual). The average total mortality coefficient (Z) for the period 1992-â€™97 was 3.3 whereas it was 3.64 during 1998-2001. The estimated fishingmortality (F) was 2.49 with exploitation ratio (F/Z) 0.756 and F 2.96 with F/Z0.815 during the same quiniqual periods respectively. During the last two yearsof 2000-2001, the rate of exploitation was very high and the average Z was3.97 with F/Z 0.814. The average F was 3.232, the yield was about 60,000 t andthe biomass was 46,391 t. The yield can be optimized at 70 % of theÂ Â currentfishing effort.